Ta’awun Curiosity Motivation: The Basis of Cooperation in Establishing Relationships for The Good - Adelia Sandra Swastika Putri; Amalia, Vindy (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This literature review examines the interactions between goal setting, curiosity motivation, human resource management (HRM), and organizational performance. The review synthesizes research on how effective goal setting increases curiosity motivation at work by aligning personal and organizational goals based on an attitude of responsibility and mutual assistance (Ta’awun), thus increasing employee engagement and performance and gaining the pleasure of Allah SWT. The review highlights the role of curiosity, a key aspect of intrinsic motivation, in fostering creativity and innovation in organizations. In addition, the review explores how HR practices such as providing supportive feedback, career development opportunities, and recognition can facilitate an environment conducive to goal achievement and intrinsic motivation. The review concludes that a strategic approach to goal setting, coupled with HR practices that foster motivation and curiosity, significantly contributes to improved organizational performance. By integrating these elements, organizations can improve employee satisfaction, productivity, and overall effectiveness, ultimately achieving superior performance outcomes.